Implementing a t-way test generation strategy using bees algorithm - Zabil M.H.M.; Zamli K.Z. (2023)
In order to ensure software performance as well as software quality, various testing techniques have been used to detect faults as early and as many as possible during the development phase. Over the last decade, the size and complexity of software developed have increased tremendously. Highly customizable software allow users to configure the software to the users' needs, however, if not tested adequately, these software are prone to interaction faults. This paper discusses our experiences on implementation of Bees algorithm for generating test cases to detect t-way interaction faults (where t signifies the interaction strength). © SCRG Publication, 2013.